2017
DOI: 10.1186/s12881-017-0370-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiles of elderly individuals subjected to indentured childhood labor and trauma

Abstract: BackgroundChildhood trauma is associated with increased vulnerability to mental and somatic disorders later in life. Epigenetic modifications such as DNA methylation are one potential mechanism through which such long-lasting impairments/consequences can be explained. The aim of the present study was to investigate whether childhood trauma is associated with long-term DNA methylation alterations in old age.MethodsWe assessed genome-wide DNA methylation profiles in a cohort of former indentured child laborers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
(53 reference statements)
1
21
1
Order By: Relevance
“…Our finding that Dlx5/6 are also important in determining healthspan and lifespan lead us to suggest that they might play an important role in establishing a fecundity/lifespan tradeoff during evolution. In this respect it is important to note that the methylation level of DLX5/6 increases in response to aging (43), metabolism (74) and life exposures (76) suggesting that these genes might be integrators of lifespan determinants. B) The quality of nests built by control, Vgat ∆Dlx5-6/+ and Vgat ∆Dlx5-6 mice was evaluated each day over a seven days period.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that Dlx5/6 are also important in determining healthspan and lifespan lead us to suggest that they might play an important role in establishing a fecundity/lifespan tradeoff during evolution. In this respect it is important to note that the methylation level of DLX5/6 increases in response to aging (43), metabolism (74) and life exposures (76) suggesting that these genes might be integrators of lifespan determinants. B) The quality of nests built by control, Vgat ∆Dlx5-6/+ and Vgat ∆Dlx5-6 mice was evaluated each day over a seven days period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a cross-sectional study by Zhang et al [34] studied 82 candidate genes in 518 individuals and found that exposure to childhood abuse in European-Americans was associated with differential methylation in both subjects with ethanol dependence and controls, while no site was differentially methylated in African-Americans. In a group of former child labourers, 71 differentially methylated CpGs were found [35].…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…Of the nine genome-wide association studies, five articles utilized a common method (Illumina HumanMethylation450 BeadChip) to analyse DNA methylation across the genome, which made them eligible for inclusion in a meta-analysis of genome-wide association studies [31,32,[35][36][37]. Cecil et al [36] kindly made summary data from their study available, and discovery data from Houtepen et al [37] were accessed from the GEO data repository (GEO Accession Number: GSE77445).…”
Section: Meta-analysis Of Genome-wide Association Studiesmentioning
confidence: 99%
“…Although a substantial body of research has accumulated linking early-life adversity to differences in DNA methylation, methods and results are heterogeneous and nonoverlapping. Under the label of “adversity,” studies have focused on a diverse mix of exposures spanning maternal psychiatric disease (13), early parental loss (14), institutionalization (15), indentured child labor (16), child abuse (17), and the Holocaust (18). On the outcome side, DNA methylation differences in surrogate tissue, such as whole blood, have been reported, but often in different genomic regions.…”
mentioning
confidence: 99%